India's National Innovation System: Key elements and corporate perspectives - Cornelius Herstatt; Rajnish Tiwari; Stephan Buse (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2008)
In recent years India has emerged as a major destination for corporate research and development (R&D), especially for multinational corporations. India's domestic institutions like Indian Space Research Organisation (ISRO), Defence Research and Development Organisation (DRDO), and the Centre for Development of Advanced Computing (C-DAC) have set prestigious milestones of international standards. Not surprisingly, at Governmental levels a number of international cooperation agreements in the field of science and technology have been signed with India. After years of self-imposed seclusion, principally motivated by post-colonial India's insistence on the development of indigenous technology, India finally seems to have joined the global mainstream of innovation. India is in the process of emerging as a major R&D hub for both large and medium-sized multinational companies in various industries. This development is mainly owing to the availability of skilled labor produced in world-class elite institutions. Cost advantages, e.g. in the form of low wages are still present but receding due to substantial wage hikes often ranging between 15 and 25% per annum. The striking finding is however about market-driven factors. Of late, India's market potential, in the meantime ranked as 3rd largest worldwide by the Global Competitiveness Report 2007-08, has emerged as a crucial driver. Rising income levels of India's billion-plus population are creating unique market opportunities for firms, both domestic and foreign. In India the Government has historically played a major and in most cases a singularly positive role in the formation of its innovation system. India, ever since its independence from British rule, has invested much time, resources and efforts in creating a knowledge society and building institutions of research and higher institutions. Despite explosive population growth literacy rate in India grew from 18.3% in 1950-51 to 64.8% in 2001 thanks to concerted Government efforts; female literacy rose from a mere 8.9% to 53.7% in the same period. Moreover the quality of education in India is generally ranked as very good. According to the Global Competitiveness Report 2007-08 the quality of mathematics and science education in India is ranked as 11th best in the world, much ahead of 29th placed Japan, 36th placed Germany, 45th placed United States and 46th placed United Kingdom. Nevertheless, India is faced with major challenges related to infrastructure and bureaucratic hurdles. The quality of education, notwithstanding such excellent rankings as stated above, in many institutions does not reach the standards required for (cutting-edge) R&D efforts. Moreover, a booming economy is leading to shortage of qualified and experienced skilled labor - which result in inflationary wage growth and high attrition rates, which generally lay in a double-digit range. With the Government maintaining a pro-active role many of these problems may however be expected to get resolved to a manageable extent. In its Eleventh Five Year Plan (2007-12) the Government has announced massive investments in infrastructure and education sectors to enhance both the quantity and the quality. Industrial firms in India have recognized their chances and are investing heavily in R&D capacities. India is also a beneficiary of global mobility and exchange of talents, technology and resources as much as the world, especially the developed Western countries, have profited from India's export of brain power. In sum all these developments raise hopes for a further improvement in the conditions of Indi's National Innovation System.
urn:nbn:de:gbv:830-tubdok-3649
Keywords: 650; National Innovation System; India; Offshoring; Globalization; Research and Development